The role of obesity as a modifying factor in patients undergoing non-surgical periodontal therapy - Zuza, Elizangela P.; Barroso, Eliane M.; Carrareto, Ana Luiza V.; Pires, Juliana R.; Carlos, Iracilda Zeppone [UNESP]; Theodoro, Letícia Helena [UNESP]; Toledo, Benedicto Egbert C. (Amer Acad Periodontology, 2011)
Background: Earlier studies have shown an association between obesity and periodontitis, which is mediated by cytokine production. The aim of this study is to assess the role of obesity as a modifying factor on periodontal clinical parameters and on circulating proinflammatory cytokine levels in subjects undergoing non-surgical periodontal treatment.Methods: Twenty-seven obese subjects and 25 normal-weight subjects were enrolled in this study. Subjects in both groups had generalized chronic periodontitis. The periodontal parameters measured before and 3 months after non-surgical periodontal therapy were: visible plaque index, bleeding gingival index, bleeding on probing, probing depth, and clinical attachment level. In addition, subjects underwent anthropometric measurements and serum analyses of fasting glucose, glycated hemoglobin, interleukin-1 beta, interleukin-6, tumor necrosis factor-alpha, and interferon-gamma.Results: Periodontal therapy significantly decreased visible plaque index, bleeding gingival index, bleeding on probing, probing depth of 4 to 6 mm, probing depth >= 7 mm, clinical attachment level of 4 to 6 mm, and clinical attachment level >= 7 mm in both groups (P <= 0.05). Circulating proinflammatory cytokines significantly decreased in obese and normal-weight subjects after periodontal treatment (P <= 0.05). However, interleukin-6 and tumor necrosis factor-a levels remained higher in obese subjects 3 months after treatment (P <= 0.05).Conclusion: Obesity does not seem to play a negative role by interfering in the improvement of the periodontal clinical response or decreasing circulating proinflammatory cytokine levels after periodontal treatment. J Periodontol 2011;82:676-682.
Keywords: Chronic periodontitis; clinical trial; cytokines; dental scaling; obesity; root planing